Hermenegildo, ¿para siempre en Sevilla? Una nueva interpretación de IHC, n. 76 = ILCV, n. 50. - Gómez Pallarès, J.; Fernández Martínez, C. (Gerión. Revista de Historia Antigua, 2001)
The authors try to analyze the different readings and interpretation of the Hermenegildus ´ inscription (it was found out in Alcalá de Guadaira, Seville) and they specially deal with the problem of its ten last letters (DVCTI AIONE), that have been misunderstood for a long time. This paper offers a new interpretation grounded on historical, archaelogical, palaeographic, epigraphic and linguistic arguments